2021
DOI: 10.4049/jimmunol.2100048
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocyte Specification Is Preceded by Extensive Epigenetic Priming in Multipotent Progenitors

Abstract: B lymphocyte development is dependent on the interplay between the chromatin landscape and lineage-specific transcription factors. It has been suggested that B lineage commitment is associated with major changes in the nuclear chromatin environment, proposing a critical role for lineage-specific transcription factors in the formation of the epigenetic landscape. In this report, we have used chromosome conformation capture in combination with assay for transposase-accessible chromatin sequencing analysis to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Both FOXO1 and EBF1 have been implicated to be ‘pioneer factors’ ( 48 , 49 ) that can open condensed chromatin and make it accessible for DNA binding proteins. While the pioneering function of EBF1 has been studied in the context of B cell development ( 48 , 54 56 ), it remains to be investigated if the Foxo family has a similar function. With ATACseq, in essence, defining open chromatin through the enrichment of reads originating from accessible regions, we utilized this to characterize how the loss of FOXO and EBF1 in the FOXOdko CLPs affected the establishment of open chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Both FOXO1 and EBF1 have been implicated to be ‘pioneer factors’ ( 48 , 49 ) that can open condensed chromatin and make it accessible for DNA binding proteins. While the pioneering function of EBF1 has been studied in the context of B cell development ( 48 , 54 56 ), it remains to be investigated if the Foxo family has a similar function. With ATACseq, in essence, defining open chromatin through the enrichment of reads originating from accessible regions, we utilized this to characterize how the loss of FOXO and EBF1 in the FOXOdko CLPs affected the establishment of open chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Both FOXO1 and EBF1 have been implicated to be ‘pioneer factors’ (Treiber et al, 2010; Hatta and Cirillo, 2007) that can open condensed chromatin and make it accessible for DNA binding proteins. While the pioneering function of EBF1 has been studied in the context of B cell development (Treiber et al, 2010; Li et al, 2018; Wang et al, 2020; Strid et al, 2021), it remains to be investigated if the FOXO family has a similar function. With ATACseq, in essence, defining open chromatin through the enrichment of reads originating from accessible regions, we utilized this to characterize how the loss of FOXO and EBF1 in the FOXOdko CLPs affected the establishment of open chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a major part of the epigenetic landscape of B-lineage-restricted genes is accessible in multipotent progenitor cells ( Strid et al 2021 ), the initiation of B-lineage specification involves substantial changes to chromosome positioning in the nucleus ( Lin et al 2012 ). This process partly depends on the C-terminal domain of EBF1 ( Boller et al 2016 ), which is reported to associate with transcriptional coactivators such as BRG1 ( Gao et al 2009 ; Wang et al 2020 ; Strid et al 2021 ) and to promote the formation of phase-separated structures at target genes ( Wang et al 2020 ).…”
Section: Creating a Path To Stable B-cell Identitymentioning
confidence: 99%